Valuing financial, health, and environmental benefits of Bt cotton in Pakistan - Shahzad Kouser; Matin Qaim (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
Data from a farm survey and choice experiment are used to value the benefits of Bt cotton in Pakistan. Unlike previous research on the economic impacts of Bt, which mostly concentrated on financial benefits in terms of gross margins, we also quantify and monetize positive externalities associated with technology adoption. Due to lower chemical pesticide use on Bt cotton plots, there are significant health advantages in terms of reduced incidence of acute pesticide poisoning, and environmental advantages in terms of higher biodiversity and lower soil and groundwater contamination. These positive externalities are valued at US 79 per acre, of which half is attributable to health and the other half to environmental improvements. Adding average gross margin gains of US 204 results in an aggregate benefit of US 283 per acre of Bt, or US 1.7 billion for the total Bt cotton area in Pakistan.
Keywords: D62; I15; Q51; Q57; 330; Bt cotton; Pesticide use; Health and environmental benefits; Choice experiment; Pakistan